2005
DOI: 10.1002/ejoc.200500093
|View full text |Cite
|
Sign up to set email alerts
|

Transannular Hydride Migration in Pseudo‐Geminally Substituted [2.2]Paracyclophanes: A Vinylogous Pinacol Rearrangement

Abstract: A vinylogous pinacol-pinacolone rearrangement is reported that takes place although the two hydroxyl groups are formally separated by seven bonds. It involves a transannular hydride shift that occurs between the benzylic positions of the pseudo-geminally substituted [2.2]paracyclophanes 1a-c,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
4
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Since the discover y of the metallic conductivity in a tetrathiafulvalene-tetracyanoquinodimethane complex [2] tetrachalcogenafulvalenes have played a leading role in the development of new molecular metals and superconductors [3][4][5]. In general, charge-transfer [6][7][8][9][10][11][12] or push-pull [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] compounds have important applications in the field of conducting materials. For these reasons heterocyclic compounds -especially those containing sulfur and nitrogen -represent an important resource for the material chemistry [30][31][32][33][34][35][36][37][38][39] and not only (biologically active compounds, daily life and even the educational process) [40][41][42][43][44][45][46][47]…”
mentioning
confidence: 99%
“…Since the discover y of the metallic conductivity in a tetrathiafulvalene-tetracyanoquinodimethane complex [2] tetrachalcogenafulvalenes have played a leading role in the development of new molecular metals and superconductors [3][4][5]. In general, charge-transfer [6][7][8][9][10][11][12] or push-pull [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] compounds have important applications in the field of conducting materials. For these reasons heterocyclic compounds -especially those containing sulfur and nitrogen -represent an important resource for the material chemistry [30][31][32][33][34][35][36][37][38][39] and not only (biologically active compounds, daily life and even the educational process) [40][41][42][43][44][45][46][47]…”
mentioning
confidence: 99%
“…In this context, a variety of acceptor units have been investigated, nitrogen and sulfur containing cations receiving a great deal of attention [9][10][11][12][13][14][15][16][17][18][19]. Of special interest for conducting materials are charge-transfer [20][21][22][23][24][25][26][27][28][29][30] and push-pull [31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47] compounds. Recent studies on (1,3-dithiolium-2yl)phenolates systems revealed that 1,3-dithiolium cations can act as acceptor groups in intramolecular chargetransfer processes [27,30,48,49].…”
mentioning
confidence: 99%
“…[18][19][20][21][22] Heteroatoms may act as auxiliary donors or acceptors and improve the overall polarizability of the chromophore. In this context, investigations on a series of (1,3-dithiolium-2-yl)phenolates showed that 1,3-dithiolium ions can also serve as an acceptor moiety in intramolecular charge-transfer systems.…”
mentioning
confidence: 99%